Pituitary adenoma with cavernous sinus compartment penetration and intracranial extension: surgical anatomy, approach, and outcomes - Yang, FuMing; Bi, YunKe; Zhou, QiangYi; Li, HongChan; Xue, YaJun; Zhu, QingWei; Yin, Jian; Wang, ZhiYu; Lou, MeiQing (Frontiers in Oncology, 2023)
Abstract Objectives: To understand the different characteristics and growth corridors of knosp grade 4 pituitary adenomas (Knosp4PA) with cavernous sinus (CS) compartments penetration and intracranial extension, aiming to improve the safety, effectiveness, and total resection rate of surgery. Methods: A case series of 120 Knosp4PA patients with 187 invaded compartments were retrospectively reviewed. A novel surgery-relevant grading system was proposed according to the CS penetrating features. The details of approach drafting, risk prediction, and complication avoidance were analyzed and integrated through illustrated cases. Results: All enrolled tumor was Knosp4PA which was derived from Knosp subgrades 3A(62.5%) and 3B(37.5%). Based on the tumor growth pathway and its relevant features, five subclassifications of intracranial extension(n=98,81.7%) were classified, which derived from the superior (Dolenc's and Oculomotor subtype, 5% and 24.2%), lateral (Parkinson's subtype,18.3%), and posterior (cerebral peduncle and Dorello's subtype, 5.8% and 1.7%) CS compartment penetration. The size of intracranial extension is assessed by Lou’s scale proposed here based on preoperative MRI characteristics. Under Lou’s scale, the gross total rate (GTR) decreased (82%, 53%, 22%, and 19%) with grades increased (grade 0,1,2,3, respectively), and presents significant difference between the four groups (p=0.000), as well as between single and multiple compartments involved (p=0.001). Preoperative cranial nerve deficits included the optic nerve (53%), oculomotor nerve (24.2%), and abducent nerve (4.2%), with an overall rate of visual function improvement in 68.1%. Postoperative complications of transient diabetes insipidus, cerebrospinal fluid (CSF) leakage, and cranial nerve deficits were 6.7%, 0.8%, and 0%. No new cranial nerve deficits occurred. The mortality rate was 0.8%. Conclusion: The concept of "penetration" refines the extracavernous growth pattern, and the five intracranial subclassifications help to understand the potential extension corridors, enhancing adequate exposure and targeted resection of Knosp4PA. This grading system may benefit from its predictive and prognostic value, from which a a higher GTR rate can be achieved.